THE EFFECT OF PACKAGING QUALITY AND PROMOTION ON BUYING INTEREST IN CISADANE STICKY RICE MSMEs - Diva Julio Rachman; Puji Isyanto; Neni Sumarni (PT. Berkah Digital Teknologi, 2025)
Purpose: This study aims to analyze the influence of packaging quality and promotion on the purchase interest of Cisadane Sticky Rice Sponge Cake MSMEs. Research Methodology: This study used quantitative research methods, by taking samples from the entire population and using a questionnaire as the main data collection tool. The population used is all 110 people interested in buying MSMEs. Results: The results show that the variables Packaging Quality (X1) and Promotion (X2) have a significant influence on the variable (Y) Purchase Interest. Limitations: The study is limited to the Cisadane Sticky Rice Sponge Cake MSMEs located in Karawang, Indonesia. Contribution: This study can be useful for MSME owners in the food and beverage industry to improve their packaging quality and promotion strategies to increase customer purchase interest.